Implementation of the PIMCA Learning Model Assisted by HOTS-based LKPD to Improve Critical Thinking Skills on Temperature and Heat Material - Resti Denis Yulianti (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Critical thinking skills are one of the skills that students must have. This skill can be trained through various scientific disciplines, one of which is physics. If we look at its characteristics, temperature and heat physics material is able to train students critical thinking skills using the knowledge and experience they have. But in reality, students consider temperature and heat material to be difficult and boring. This is due to lack of student involvement and lack of student understanding of temperature and heat material. Therefore, this research aims to determine the improvement of students' critical thinking skills through the use of the PIMCA learning model assisted by HOTS-based LKPD on temperature and heat material. The research method used is quantitative with a one group pretest-posttest design. The research instrument is a critical thinking skills test in the form of an essay. Data analysis of critical thinking skills test results includes normality testing, hypothesis testing, and continues with the n-gain test to obtain in-depth information regarding students critical thinking skills. In general, the research results show that the average critical thinking skills of students is 0.76 in the high category. High levels of critical thinking skills can be seen in the categories of elementary clarification, basic support, inference, and strategy and tactics. Meanwhile, students critical thinking skills in the category of advanced clarification are still in the medium category.